Potential of caveolae in the therapy of cardiovascular and neurological diseases - Navarro, Gemma; Borroto-Escuela, Dasiel O.; Fuxe, Kjell; Franco, Rafael (Frontiers in Physiology, 2014)
Caveolae are membrane micro-domains enriched in cholesterol, sphingolipids and caveolins, which are transmembrane proteins with hairpin-like structure. Caveolae participate in receptor-mediated trafficking of cell surface receptors and receptor-mediated signaling. Furthermore, caveolae participate in clathrin-independent endocytosis of membrane receptors. On the one hand, caveolins are involved in vascular and cardiac dysfunction. Also, neurological abnormalities in caveolin-1 knockout mice and a link between caveolin-1 gene haplotypes and neurodegenerative diseases have been reported. The aim of this article is to present the rationale for considering caveolae as potential targets in cardiovascular and neurological diseases.